Adubação da mandioca (Manihot utilissima Pohl.) I: ensaio em areia lavada (Nota prévia) - Malavolta, E.; Coury, T.; Graner, E. A.; Pacheco, J. A. de C.; Brasil Sobr., M. O. C. do (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1952)
This paper deals with the preliminary results of a sand culture experiment carried out to obtain physiological bases to study the fertilization of cassava in the State of São Paulo. On the other hand, the authors are interested in the possible influence of mineral nutrients in the quantity and quality of starch. Cassava (Manihot utilissima Pohl.), "Branca de Sta. Catarina" variety, was grown under the following treatments: NO PO KO, NO P1 K1, N1 P0 Kl, NI P1K0, N2 p1 Kl N1 P2 K1 and N1 P1 K2. A striking response to phosphorus was observed among the treatments. However, once secured the necessary phosphoric level to the plant, the production becomes limited by nitrogen; in other words, increase in yield can be accomplished only by raising the nitrogenous level. The present results suggest that the remarkable effects of phosphates applied to cassava cultures in the State of São Paulo are due not only to the poor quality of our soils, as far phosphorus is concerned: we are facing a positive physiological response showed by the plant.